Moderasi Internal Beragama Perspektif ‘Abd al-Rahmân al-Sudais, Presiden Urusan Dua Masjid Suci: Internal Moderation of Different Religion Perspective ‘Abd Al-Rahman Al-Sudais, President of the Two Holy Mosques - Rahendra Maya; Mufid, Mufid; Samsuddin, Samsuddin; Muhammad Fadilah Al-Farisi (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
‘This research aims to examine the concept of moderation (al-wasathiyyah) in the thoughts of Sheikh Abdul Rahman Al-Sudais, particularly regarding internal moderation among Muslims with differing ideological orientations, as well as the steps for its implementation in the Kingdom of Saudi Arabia. (KAS). This research employs a qualitative method through a descriptive-interpretative approach, utilizing documentary data collection techniques and analyzing it using content analysis techniques. (content analysis). The findings of this research indicate that through his work, Al-Sudais narrates religious moderation as an Islamic conception aimed at maintaining security for all parties, particularly through the revitalization of intellectual resilience (ta’zîz al-amn al-fikrî); or specifically to avoid the phenomena of radicalism and intolerance. In addition to external religious moderation among followers of different faiths, Al-Sudais also examines internal religious moderation among Muslims with differing Islamic thought orientations. Serta presents its strategic steps within the scope of the Kingdom of Saudi Arabia (KSA), namely through (1) KSA's active role in countering the movements of apostasy and terrorism; (2) KSA's full support for the implementation of moderation dialogue; and (3) KSA's special attention to the issues faced by women.